Teaching Mathematics Using a Strategy Compatible with the Brain Hemispheres Approach and Its Effect on Developing Information Processing Skills Among Eighth Grade Basic Students - Ibrahim, Azhar Ali Hussein (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: This study investigated the effect of a brain hemispheres-compatible teaching strategy on developing information processing skills among eighth-grade mathematics students. The approach aims to engage both left-hemisphere functions (logical reasoning, sequential processing) and right-hemisphere functions (spatial reasoning, holistic thinking) to enhance mathematical learning during the critical developmental period of early adolescence. Methods: The research employed a quasi-experimental design with two equivalent groups at Avro School (2022-2023): an experimental group (30 students) taught using the brain hemispheres strategy and a control group (29 students) taught using traditional instruction. Assessment utilized a validated 25-item test measuring four information processing skills: summarization, application, pattern recognition, and interpretation. The experimental intervention followed six phases: preparation, engagement, learning design, acquisition, memory formation, and functional integration. Results: Statistical analysis revealed significant differences favoring the experimental group (t=5.988, p<0.05) with a very large effect size (η²=0.38). The experimental group showed significant improvement across all four information processing skills with effect sizes ranging from 1.19 to 2.19. Conclusion: The brain hemispheres-compatible teaching strategy proved highly effective in developing students’ mathematical information processing skills by creating organized mental frameworks that facilitate knowledge integration and cognitive development.